2011
DOI: 10.5665/sleep.1444
|View full text |Cite
|
Sign up to set email alerts
|

Poor Self-Reported Sleep Quality Predicts Mortality within One Year of Inpatient Post-Acute Rehabilitation among Older Adults

Abstract: Poorer self-reported sleep quality, but not objectively estimated sleep parameters, during post-acute rehabilitation was associated with shorter survival among older adults. This suggests self-reported poor sleep may be an important and potentially modifiable risk factor for negative outcomes in these vulnerable older adults. Studies of interventions to improve sleep quality during inpatient rehabilitation should therefore be undertaken, and the long-term health benefits of improved sleep should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 24 publications
1
61
0
Order By: Relevance
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
“…Sleep problems in various general populations with and without chronic diseases have been associated with poorer self-rated health 5 and with increased mortality. 6,7 Without appropriate treatment, sleep problems can become persistent, as reported by Morin et al, 8 who found that 49% of patients with insomnia symptoms at baseline had insomnia symptoms at the 1-year follow-up as well. Elderly people with chronic conditions are at risk of developing persistent sleep disturbances, 9 and sleep disturbances have been associated with increased costs for healthcare utilization in samples with and without chronic disease.…”
mentioning
confidence: 76%
“…In our prior work, we found that sleep disruption in the post-acute care setting was associated with less improvement in functioning and shorter survival over the year following discharge from post-acute rehabilitation. 11;12 …”
Section: Objectivementioning
confidence: 99%